The Differences in Stock Market Performance: A Comparative Study on Capital Market - Mister Candera, Abid Djazuli, Ervita Safitri, (Opción, 2019)
The purpose of this study was to examine the differences in stock market performance in the capital market in several countries. This research is a comparative study that aims to compare one or more variables in two or more different samples, or at different times. The results reveal there were differences in stock performance with the Sharpe and Jensen methods, while using the Treynor method there was no difference. In conclusion, the combined test results for all three methods show that there is no difference in stock market performance between several countries.